Fabrication of Agricultural Waste-Based Biobriquettes Using Tapioca Starch Adhesive - Asmara, Sandi; Tamrin; Warji; Muhammad , Fazle; Amien, Elhamida Rezkia (Open Science and Technology, 2025)
Background: Energy demand continues to increase along with population growth and human activities, while the availability of fossil energy in Indonesia is becoming increasingly limited. On the other hand, agricultural biomass wastes such as cassava stems, bamboo stems, coconut shells, and corn cobs are abundantly available but have not yet been optimally utilized as alternative energy sources.Aims: The aim of this research is to to evaluate the effect of combining biomass wastes of cassava stems, bamboo stems, coconut shells, and corn cobs using tapioca starch as a binder on the physical characteristics and energy value of biobriquettes, as well as to assess their conformity with briquette quality standards as an alternative fuel.Methods: This study produced biobriquettes from cassava stems, bamboo stems, coconut shells, and corn cobs using tapioca starch as a binder with two concentrations (7% and 10%). The biobriquettes were evaluated for physical and energy characteristics, including density, moisture content, compressive strength, shatter resistance index, calorific value, and burning rate, following SNI 01-6235-2000.Result: Evaluation of biobriquette quality based on SNI 01-6235-2000 shows that all treatments meet the requirements for density, moisture content, and Shatter Resistance Index, indicating good physical quality and mechanical durability. For calorific value, only treatments P2T1, P2T2, P3T1, and P3T2 meet the minimum SNI standard (? 5,000 cal/g), while P1T1 and P1T2 do not. Overall, the biobriquettes produced have the potential to comply with SNI 01-6235-2000 as an alternative fuel, although optimization of biomass composition is still needed to improve calorific value.Conclusion: The combination of cassava stems, bamboo stems, coconut shells, and corn cobs using tapioca starch as a binder was able to produce biobriquettes suitable as an alternative fuel. Treatments P2 and P3, particularly with a 7% binder concentration, met the calorific value requirement of SNI 01-6235-2000, indicating that a lower tapioca binder concentration is more effective and has strong potential for development as a renewable energy source based on biomass waste.